Adaptation of ruls-6 loneliness scale (6-item short form) into turkish: a validity and reliability study - EKŞİ, HALİL (My University, 2022)
This study includes the adaptation of the 6-item UCLA (Developing a Measure of Loneliness) loneliness scale developed into the Turkish language and the findings of its reliability and validity values. The study was conducted with the data obtained from the study group (n = 327), including university students. As a result of the analyses, it was determined that the scale showed a single-factor structure in accordance with its original structure. Furthermore, the criterion validity of the scale is also computed using the UCLA loneliness scale version 3. The reliability of the scale was computed by Cronbach’s alpha coefficient technique and it was found to be .84. Findings have shown that the Turkish adaptation of the 6-item UCLA loneliness scale is reliable and valid and can be used in measuring loneliness in Turkey.
Keywords: Loneliness; scale adaptation; validity; reliabilit